2019
DOI: 10.21425/f5fbg43737
|View full text |Cite
|
Sign up to set email alerts
|

The effect of small-scale topography on patterns of endemism within islands

Abstract: • Small-scale variation in topography may favour endemism if it causes species to be persistently isolated • La Palma (Canary Islands) has many deep, steep-sided barrancos, containing unique habitat with many endemic plant species • The proportion of endemic plants on barranco floors decreases with elevation, while the co-linear increase with barranco depth is not significant • Local topography may complicate broader-scale relationships between endemism and elevation, and this requires further research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Cliffs in the Mediterranean are considered refugia for plant species with unique species composition [58]. Vertical cliffs and rocky habitats in a landscape contribute to the isolation of open habitats and increase fragmentation among patches, but also consist of habitat islands, often isolated, which are themselves separated from each other by dispersal barriers, creating divergence between resident populations [59] and having the potential to harbor relatively high levels of endemism [60].…”
Section: Chasmophytic Flora Of the Aegean Species Richness Life Forms And Chorologymentioning
confidence: 99%
See 2 more Smart Citations
“…Cliffs in the Mediterranean are considered refugia for plant species with unique species composition [58]. Vertical cliffs and rocky habitats in a landscape contribute to the isolation of open habitats and increase fragmentation among patches, but also consist of habitat islands, often isolated, which are themselves separated from each other by dispersal barriers, creating divergence between resident populations [59] and having the potential to harbor relatively high levels of endemism [60].…”
Section: Chasmophytic Flora Of the Aegean Species Richness Life Forms And Chorologymentioning
confidence: 99%
“…Kallimanis et al [76] found that neo-endemics, as a proportion of the islands' flora, is associated only with the islands' maximum elevation and that neoendemic species richness is also strongly correlated to island area and diversity of geological substrate, indicating that an island's habitat heterogeneity is the main environmental driver of speciation. The effect of large-scale topography such as mountain ranges on patterns of species richness, speciation rates, and endemism are increasingly well documented [39,42,57,[77][78][79][80], but the direct effect of local topography such as ravines is less well understood [60], although areas with larger variation in elevation are thought to have higher speciation and endemism rates [81].…”
Section: Elevational Gradients and Spatial Turnover Of Chasmophytic Diversity: Monitoring Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, on oceanic islands, such as the Galápagos islands, habitat filtering proved to be more important than dispersal limitation in determining the species composition of plant assemblages (Carvajal-Endara et al, 2017). Thus, habitats within each island can differ in species composition (e.g., Cutts et al, 2019) and have also been referred to as "habitat islands" (Kontopanou and Panitsa, 2020). Since the species-area relationship predicts that larger habitats support higher species richness, the species richness of each habitat within an island is controlled by the area, by a Habitat Species-Area Relationship (HSAR).…”
Section: Introductionmentioning
confidence: 99%